Basal metabolic rate for adolescents with overweight or obesity (Research, Society and Development, 2021)
The basal metabolic rate (BMR) represents the main component of energy expenditure (SG) in humans and, therefore, has great relevance in obesity treatment programs. Despite this, there are few studies that present data related to BMR of overweight or obese adolescents. Therefore, the objective of the present study is to present information about BMR of adolescents aged between 10 and 18 years old, of both sexes, with a BMI between 25.3 and 52.5 kg / m2. 91 adolescents were evaluated using the indirect calorimetry (CI) method, 37 boys and 54 girls. The prevalence of overweight was 23.0%, obesity 36.3% and severe obesity (40.6%). The median BMR was 2,150.9 and 1,548.4 for boys and girls, respectively (p